A comparative study of depression among the elderly living in old age homes and community in Visakhapatnam, India - Karini, Deepthi; Kumar Lotheti, Siva; Bhimarasetty, Devi Madhavi (International Journal Of Community Medicine And Public Health, 2019)
Background: Depression in old age is an emerging public health problem leading to morbidity and disabling effect on the quality of life. Depression in elderly is not yet perceived as a public health problem and is grossly underdiagnosed and undertreated. The physical and social environment plays an important role on the mental health of the elderly. Hence the present study was undertaken to assess and compare the depression among elderly residing in old age homes (OAHs) and community. The objective of the study was to assess and compare depression among elderly residing in OAHs and those living in community. Methods: A cross sectional study was done from October to December, 2016 among 100 elderly, of which 50 were inmates of old age homes and 50 were living in community selected by house to house survey. A pre tested, externally validated short form geriatric depression scale (GDS-15) in the local language is used after taking informed consent. Results: Prevalence of depression was high among inmates of old age homes (80%) compared to those of community (52%), this difference was statistically significant (p=0.003). On analyzing the association between sociodemographic factors and depression among the elderly residing in the community, it was found that marital status and presence of chronic disease were significantly associated with depression (p<0.05). Whereas among the elderly residing in old age homes, no significant asociation was found between depression and the sociodemographic factors. Conclusions: High prevalence of depression observed among the studied population indicates the need of screening for depression among elderly.